2020
DOI: 10.1002/elan.202060032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Analysis of Hydrogen Evolution Reaction on Pt in HClO4 Using Inverted Rotating Disc Electrode

Abstract: An inverted rotating disc electrode (IRDE) setup was fabricated to study the hydrogen evolution reaction (HER) on a Pt electrode. Potentiodynamic polarization studies were conducted in solutions from 5 to 100 mM HClO4 on Pt at three different rotational speeds. Periodic anodic activation of the electrode yielded repeatable results. At high currents, bubble formation adversely affects current measurement in the rotating disc electrode, but not in IRDE. At large cathodic overpotentials, HER current in IRDE is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The linearity reveals that H 2 evolution follows first order reaction and a noticeable change in j k is observed. 23 The fresh catalysts show an increase in the electron transfer rate with increasing overpotential, whereas in the catalysts after chronoamperometry, the observed constant j k values (with overpotential), implying a rapid electron transfer. The obtained Levich slope ( B ) and transferred electrons number ( n ) ( n < 1) (0.72 < n < 0.94) suggest that the Volmer reaction become the rate-limiting step.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The linearity reveals that H 2 evolution follows first order reaction and a noticeable change in j k is observed. 23 The fresh catalysts show an increase in the electron transfer rate with increasing overpotential, whereas in the catalysts after chronoamperometry, the observed constant j k values (with overpotential), implying a rapid electron transfer. The obtained Levich slope ( B ) and transferred electrons number ( n ) ( n < 1) (0.72 < n < 0.94) suggest that the Volmer reaction become the rate-limiting step.…”
Section: Introductionmentioning
confidence: 89%
“…Yan et al reported that HER could be diffusion limited when the electrode kinetics becomes fast, as evidenced by the rotation speed dependent HER current on Pt in acid and the overlap of HER polarization curve with concentration overpotential curve. 23 The diffusion limitation of HER originated from the slow mass transport of produced H 2 on the electrode to the bulk electrolyte and the reversible nature of HOR/HER. Though the diffusion overpotential for HER becomes small, it has a significant impact on kinetic analysis in the low overpotential region, leading to inaccurate mechanistic interpretations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations